Writing Around the Ancient Mediterranean - Steele, Philippa M. (Oxbow Books, 2022)
Writing in the ancient Mediterranean existed against a backdrop of very high levels of interaction and contact. In the societies around its shores, writing was a dynamic practice that could serve many purposes – from a tool used by elites to control resources and establish their power bases to a symbol of local identity and a means of conveying complex information and ideas. This volume presents a group of papers by members of the Contexts of and Relations between Early Writing Systems (CREWS) research team and visiting fellows, offering a range of different perspectives and approaches to problems of writing in the ancient Mediterranean. They focus on practices, viewing writing as something that people do within a wider social and cultural context, and on adaptations, considering the ways in which writing changed and was changed by the people using it.